Establishment of diuretic activity indicators for (3-thio-4-R-4-H-1,2,4-triazole-5-yl)(phenyl)methanols and their derivatives - A. M. Rud; A. G. Kaplaushenko; Ye. S. Pruglo; Yu. S. Frolova (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Diuretic drugs are drugs that, by blocking the transport systems of the renal tubules, promote the removal of excess electrolytes and water from the body, normalization of the internal environment. They eliminate edema, reduce the fluid content in the body cavity. Diuretic drugs differ in their chemical structure, the mechanism of action on the urinary tract function of the kidneys and on the mechanisms of regulation of this function. It should be noted that the use of the above mentioned agents can lead to undesirable side effects, such as nausea, vomiting, unpleasant sensations in the stomach, headache, facial hyperemia.